Peramalan Produksi Beras Indonesia Tahun 2024: Pemenuhan Target Produksi Beras Nasional dan Upaya Mencapai Kemandirian Pangan - Putri, Aida Devanty; Haya, Aqilla; Crisanty, Tengku Mashitah (Politeknik Statistika STIS, 2024)
To ensure food independence, achieving production sufficiency is essential. The government has targeted rice as the primary commodity for self-sufficiency. This study aims to estimate rice production up to December 2024 to evaluate Indonesia’s potential in achieving food independence through the 2024 rice production target. Utilizing rice production data from 2019 to April 2024 provided by BPS-Statistics Indonesia, the study employs SARIMA model (2,0,0)(0,1,1)12. The findings suggest that rice production in Indonesia is projected to reach only approxiamtely two-thirds of the national production target for 2024, and indicating a decreased in rice compared to 2023. The literature review underscores the need for strategies such as increasing the availability of land rice cultivation, diversifying food source to reduce dependence on rice, and the implementing technological innovations and information systems to enhance food diversity.